Angiogenesis in ischemic diabetic foot syndrome in patients after endovascular revascularization of lower limb arteries - Schönborn, Martyna (2024)
One of the main treatment forms for the ischemic diabetic foot' syndrome (DFS) is percutaneous transluminal angioplasty (PTA), but its outcomes are not always satisfactory. This may be influenced by microcirculatory dysfunction and an inadequate process of angiogenesis in wound healing. This study summarizes the current knowledge on the changes in the levels of angiogenic factors among patients with DFS, investigates selected circulating angiogenic factors and microcirculation parameters in the context of the severity of DFS, and explores their relationship with ulcer healing and poor outcomes during a one-year follow-up after PTA. The research showed higher concentrations of circulating fibroblast growth factor 2 (FGF-2) among patients with deep ulcers and those who experienced poor outcomes after PTA. There was also a trend towards higher values of circulating vascular endothelial growth factor A (VEGF-A) and transcutaneous oximetry (tcpO2), as well as lower concentrations of pigment epithelium-derived factor (PEDF) among patients who did not experience a composite poor outcome after PTA. The results of this study indicate a significant involvement of disturbed angiogenesis in the ulcer healing process in patients with DFS after PTA and may form the basis for further research on the use of angiogenic factors to assess the progression of ischemic DFS and to monitor treatment o
Keywords: angiogenesis; diabetic foot syndorme; revascularization; microcirculation